2021
DOI: 10.1016/j.jbc.2021.101299
|View full text |Cite
|
Sign up to set email alerts
|

The Sigma-1 receptor is an ER-localized type II membrane protein

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 47 publications
1
18
0
Order By: Relevance
“…Sig1R was cloned in 1996 [ 38 ], while the crystal structure of full-length human Sig1R was published in 2016 [ 39 ]. Very recently, it was shown that Sig1R is an ER-localized type II membrane protein [ 40 ]. Nevertheless, there is no consensus about the dynamics of Sig1R within the cell.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sig1R was cloned in 1996 [ 38 ], while the crystal structure of full-length human Sig1R was published in 2016 [ 39 ]. Very recently, it was shown that Sig1R is an ER-localized type II membrane protein [ 40 ]. Nevertheless, there is no consensus about the dynamics of Sig1R within the cell.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there is no consensus about the dynamics of Sig1R within the cell. On the other hand, there is quite a good consensus that Sig1R is an ER protein that acts as a molecular chaperone and forms cholesterol-enriched microdomains in the ER membrane [ 12 , 31 , 40 ]. However, most of the evidence regarding the dynamics of Sig1R obtained with different cell imaging techniques is indirect as dynamic changes occurring remain below the diffraction limit of light microscopy and therefore cannot be clearly characterized.…”
Section: Discussionmentioning
confidence: 99%
“…BirA and Sec-BirA plasmids were a kind gift from Gianlucca Petris and Oscar Burrone (ICGEB, Trieste, Italy) (21). H2a-BAP was cloned in pcDNA3.1 using restriction enzymes EcoR1 and XbaI for H2a(G78R) followed by a C-terminal BAP-SV5 tag using XbaI (39).…”
Section: Methodsmentioning
confidence: 99%
“…. H2a-BAP was cloned in pcDNA3.1 using restriction enzymes EcoR1 and XbaI for H2a(G78R) followed by a C-terminal BAP-SV5 tag using XbaI (39).…”
Section: Plasmids and Constructsmentioning
confidence: 99%
See 1 more Smart Citation